Analysis of congruency effects of corporate responsibility code implementation on corporate sustainability in bio-economy - Nicoleta Cristache; Marian Năstase; Radu Petrariu; Margareta Florescu (Amfiteatru Economic Journal, 2019)
The present study attempts at providing an overview of the congruency effect of social reporting on corporate sustainability in bio-economy. The paper was structured to identify the main congruency forces that can constitute both the strategic and operational dimensions linked to the implementation of a corporate responsibility code within companies from the bio-economy sector. Research has shown that the congruency effect is stronger when companies report a greater tendency towards social reporting and pay more attention to the relationships with stakeholders. Moreover, the results of the study aimed to shed a new light on the role of a company's social identity both in its internal process and in consolidating its position in the market by using CSR reporting elements.
Keywords: M14; Q56; 330; corporate responsibility code; bio-economy; congruency effect; sustainability